(untitled) (Global Journal of Medical Research, 2023)
This article presents the results of a study of the peculiarities of cardiac rhythm and conduction disturbances in professional football players performing in specific energy-intensive positions on the field. The correlation of the revealed violations on the electrocardiogram with the presence of bradycardia and the level of physical performance was carried out. It was found that among football players playing in the positions of a defensive midfielder and a lateral defender, both rhythm and conduction disturbances, which characterize a high degree of heart adaptation to physical stress, and disturbances that are an indicator of maladjustment to stress, are expressed.